Abstractive Text Summarization of Indonesian News Articles Using Long Short-Term Memory (LSTM) - Mahardika, I Gede Surya; Sasmita, Gusti Made Arya; Piarsa, I Nyoman (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 6 No 1 (2025): JITTER, Vol.6, No.1, April 2025, 2025)
The digital era is characterized by an increasing number of news articles available online, causing information overload problems for readers. To overcome this problem, this research develops an abstractive text summarization system on Indonesian news articles with the Long Short-Term Memory (LSTM) method with additional FastText word embedding and Attention Layer. The dataset used amounted to 105,588 news article data, which was collected through a web scraping process from the Detik.com news site. The model was developed in sequence-to-sequence architecture (Seq2Seq) and tested in four variations, namely: Basic Seq2Seq LSTM (no additions), LSTM with FastText embedding, LSTM with Attention Layer, and LSTM with FastText and Attention Layer combination. The best model is the LSTM model with Attention Layer using 80:20 data distribution with ROUGE-1 accuracy of 0.5207, ROUGE-2 of 0.4000 and ROUGE-L of 0.4970. The results show that the LSTM model with Attention Layer provides better performance in generating summaries. Thus, this research contributes to the development of abstractive text summarization system in Indonesian language. Keywords : Abstractive Text Summarization, LSTM, FastText, Attention Layer, ROUGE